Effects of soil tillage on soil compaction, available soil water, and development of common bean - Stone, Luis Fernando; Silveira, Pedro Marques da (Pesquisa Agropecuaria Brasileira, 1999)
The effects of three tillage methods (moldboard ploughing, disking, and no-tillage) on soil compaction, available soil water, root development, and common bean (Phaseolus vulgaris L.) yield were evaluated. The experiment was carried out on a Dark Red Latosol, under center pivot sprinkler irrigation, which allows cropping twice a year. The soil under moldboard ploughing showed the lowest resistance to penetration throughout the profile, whereas under disking the soil showed a compacted layer between 10 and 24 cm deep. Higher compaction until 15-22 cm was observed under no-tillage. Crop roots were more uniformly distributed throughout the soil profile under moldboard ploughing, whereas under disking and no-tillage roots concentrated in the top 10 and 20 cm of soil, respectively. The lowest resistance to penetration and the more uniform root distribution throughout the soil profile under moldboard ploughing did not reflect on higher yield of common bean as compared to the other tillage methods, when under irrigation. The highest yield observed under no-tillage was due, in part, to the lower values of soil water matrix tension observed, and to the smaller variation in this parameter all over the crop cycle, as opposed to the other methods of soil tillage.